1999
DOI: 10.1046/j.1365-2842.1999.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissue health in reconstructed atrophic maxillae—report of 88 patients and 470 implants

Abstract: The aim of this study was to evaluate the soft-tissue health around 470 implants placed in the upper jaw of 88 patients with severe maxillary atrophy. All patients underwent a reconstruction procedure which included a composite bone grafting from the iliac crest to the maxillary sinus. Evaluation was performed at a mean implant lifetime of 21.6+/-10.9 months. The following parameters were used: probing depth, plaque-, gingival-, bleeding index and width of the buccal keratinized mucosa. They were calculated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…This represents the classical clinical manifestation of peri-implant pathology, namely, DP accumulation, followed by B resulting from gingival inflammation and PIP formation. This finding was previously reported (2,53,54). The type of mucosa (keratinized vs. non-keratinized) might also be important in disease incidence and development; however, our study did not investigate mucosa type, and thus the effect of this variable is unknown.…”
Section: Discussionsupporting
confidence: 51%
“…This represents the classical clinical manifestation of peri-implant pathology, namely, DP accumulation, followed by B resulting from gingival inflammation and PIP formation. This finding was previously reported (2,53,54). The type of mucosa (keratinized vs. non-keratinized) might also be important in disease incidence and development; however, our study did not investigate mucosa type, and thus the effect of this variable is unknown.…”
Section: Discussionsupporting
confidence: 51%
“…In many cases, performing oral hygiene was reported to be painful as a result to the absence of the keratinized tissue surrounding the implant. Moreover, discomfort has been related to mechanical irritation due to the mobility of the nonkeratinized tissue under function [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…There was a significantly higher gingival index and probing depth in overdenture versus fixed prosthesis cases [18]. It has been reported that implants supporting overdentures had more risk for bone loss, based on poorer peri-implant tissue health [18]. Adibrad et al investigated the association between the width of the keratinized tissue and the health status of the soft tissue around implants supporting overdentures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in many cases tooth-brushing is painful for these patients because of the thin buccal mucosa, which is often formed after implant placement procedures. 7 For many years the presence of an ''adequate'' zone of gingiva was considered critical for the maintenance of gingival health and prevention of periodontal disease progression. Friedman 8 stated that ''inadequate'' zone of gingiva would facilitate subgingival plaque formation because of improper pocket closure resulting from the movability of the marginal tissue.…”
mentioning
confidence: 99%